2021
DOI: 10.3389/fnhum.2020.604639
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Consumer Preference by Analysis and Classification EEG Signals

Abstract: Neuromarketing has gained attention to bridge the gap between conventional marketing studies and electroencephalography (EEG)-based brain-computer interface (BCI) research. It determines what customers actually want through preference prediction. The performance of EEG-based preference detection systems depends on a suitable selection of feature extraction techniques and machine learning algorithms. In this study, We examined preference detection of neuromarketing dataset using different feature combinations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 35 publications
0
50
0
Order By: Relevance
“…Based on previous studies on the role of asymmetric frontal cortical activity in emotional and motivational processes, Harmon- Jones and Gable (2018) assert that much research supports the view that greater left than right frontal cortical activity is associated with greater positively or negatively valanced approach motivation. This is further supported by Aldayel et al (2021) where they state that: "Several studies have shown the efficacy and precision of frontal alpha asymmetry as an essential determinant in emotion and neuromarketing research. "…”
Section: Subconscious Measure Of Evaluation: Recording Alpha Asymmetry Using Electroencephalographymentioning
confidence: 81%
“…Based on previous studies on the role of asymmetric frontal cortical activity in emotional and motivational processes, Harmon- Jones and Gable (2018) assert that much research supports the view that greater left than right frontal cortical activity is associated with greater positively or negatively valanced approach motivation. This is further supported by Aldayel et al (2021) where they state that: "Several studies have shown the efficacy and precision of frontal alpha asymmetry as an essential determinant in emotion and neuromarketing research. "…”
Section: Subconscious Measure Of Evaluation: Recording Alpha Asymmetry Using Electroencephalographymentioning
confidence: 81%
“…In neuromarketing, PSD is one of the most common feature extraction methods ( Khushaba et al, 2012 ; Yılmaz et al, 2014 ; Golnar-Nik et al, 2019 ). The brain asymmetry-based preference indices such as approach-withdrawal (AW) index, valence, choice index, and effort index are also used as features to predict consumer’s preference ( Aldayel et al, 2020 , 2021 ). Besides, EEG features such as DE and Hjorth parameters have generally been used in some EEG-based applications ( Chen et al, 2019 ; Joshi and Ghongade, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…The effort index measures effort and cognitive processing as higher theta activation in the prefrontal cortex. We used the following equation to calculate the effort index ( Aldayel et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, EEG signals could also be used to detect psychological and physiological diseases [5,7], which played an important role in the advanced knowledge and treatment of major depression [2,3], autism [1], schizophrenia [8], Parkinson's syndrome [9] and epilepsy. In addition, EEG signals can be used to measure emotion recognition [10][11][12] and sleep quality [13], and had important applications in neuromarketing [14], biometrics [15] and brain-computer interface and games [16].…”
Section: Introductionmentioning
confidence: 99%